2022
DOI: 10.1186/s12903-022-02370-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the French version of COHIP-SF-19 among 12-years children in New Caledonia

Abstract: Background Assessment of oral health-related quality of life is now associated to clinical indicators in epidemiological studies. This study aimed at validating the French Short Form of the Child Oral Health Impact Profile (COHIP-SF-19) and assessing the impacts of oral diseases among schoolchildren in New Caledonia (NC). Methods A sample of 12-years-old children (n = 971) was selected in 2019 in NC using a random, stratified, and clustered samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Thiruvenkadam et al [ 26 ] evaluated the oral health-associated quality of life of children who sought orthodontic treatment, and found no statistically significant difference in COHIP SF scores between girls and boys and The results of the current study agrees as the only positive correlation was observed between oral health scores and sex in the fixed appliance group at base line where the scores were higher in females than in males. In contrast, the COHIP-SF-19 levels were lower in girls than in boys in the New Caledonia COHIP-SF-19 validation study while, the Japanese COHIP-SF-19 validation research indicated greater results for girls [ 25 , 27 ]. Previous research that used the Chinese COHIP-SF 19 noticed no gender differences in total or socio-emotional well-being subscores; however, females had higher functional well-being and oral health subscores than males [ 28 ].…”
Section: Discussionmentioning
confidence: 97%
“…Thiruvenkadam et al [ 26 ] evaluated the oral health-associated quality of life of children who sought orthodontic treatment, and found no statistically significant difference in COHIP SF scores between girls and boys and The results of the current study agrees as the only positive correlation was observed between oral health scores and sex in the fixed appliance group at base line where the scores were higher in females than in males. In contrast, the COHIP-SF-19 levels were lower in girls than in boys in the New Caledonia COHIP-SF-19 validation study while, the Japanese COHIP-SF-19 validation research indicated greater results for girls [ 25 , 27 ]. Previous research that used the Chinese COHIP-SF 19 noticed no gender differences in total or socio-emotional well-being subscores; however, females had higher functional well-being and oral health subscores than males [ 28 ].…”
Section: Discussionmentioning
confidence: 97%
“…In accordance with our findings, validation studies of the COHIP-SF-19 have reported these two items were the most unanswered questions. It has been suggested that these two items are the only positively worded questions, which could potentially confuse participants (62).…”
Section: Discussionmentioning
confidence: 99%
“…The COHIP (Community Oral Health Improvement Plan), which was originally developed to assess "oral-facial well-being" across a range of ages (8-15 years) and ethnicities [19][20][21][22], is also a comprehensive and well-validated questionnaire for determining children's OHRQoL. It contains 34 questions and 5 subscales (oral health, functional well-being, socio-emotional well-being, school environment, and self-image).…”
Section: Introductionmentioning
confidence: 99%
“…For the interpretation of this questionnaire, we have, on the one hand, to analyze the final score of the questionnaire. On the other hand, we must also analyze the average score of each dimension and the score of each question individually [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%